Contentious Connectivity—the USA, Japan, and the Free and Open Indo-Pacific - Gaens Bart; Sinkkonen Ville (Springer Nature, 2025)
This article explores how the USA and Japan have aimed to advance connectivity and infrastructure investment in the Indo-Pacific, implicitly or explicitly in response to China’s Belt and Road Initiative (BRI). Both actors’ vision, strategies, and policies have been rolled out under the banner of the “Free and Open Indo-Pacific” (FOIP). The article first frames connectivity and the FOIP construct in the context of regional order and great-power relations in the Indo-Pacific. It then provides an in-depth assessment of the different initiatives by the USA and Japan, scrutinizing their progress on the ground, shortcomings, and relevant interlinkages. After an analysis of the logics that inform these connectivity initiatives, the article offers three key axioms and assesses implications for order more broadly. First, the West must fix the gap that often exists between rhetoric and capabilities in the sphere of infrastructure investments. Second, Western actors, including the USA and Japan, need to be clear about objectives. Namely, they must decide whether the aim of connectivity is to compete directly with China or to focus on complementarities and comparative advantages. Third, the USA and Japan need to prioritize connections and spheres of connectivity that are deemed strategically central, at the expense of others. More generally, given the connective logics that key actors currently harness, a fracturing of the region into one of the different orders comprising competing yet overlapping connections beckons.